Treatise on the Marvelous for Prestigious Museums - Remein, Daniel C. (punctum books, 2018)
Wrapped in modernist architect Marcel Breuer's 1971 addition to the Cleveland Museum of Art, A Treatise on the Marvelous for Prestigious Museums considers the global ecological catastrophe by way of a speculative address to the art museums of the future, revisiting mid-century modes of site-specificity and speculative collage as utopian practices for the present. Written over the course of a decade, the book insists on the continuing importance of the New American Poetry and Language poetics, and includes work in the tradition of the ongoing serial poem and documentary poetics. This full color edition reproduces the maps, diagrams, and facsimiles that adorn the treatise.